(untitled) (ModaPalavra e-periódico, 2022)
From the 1980s onwards, the textile industry underwent a deep expansion due to the consolidation of fast fashion, causing the lifespan of clothes to reduce by 35%. As a result, today the textile sector is the second most polluting to the environment, behind the oil industry. In Brazil, it is estimated that 160 thousand tons are generated per year, 60% of which are destined for landfills. Facing such a problem, the Circular Economy (CE) presents itself as a better alternative to the current linear economic model. The entire production system must be covered for CE to be implemented, at the macro, meso and micro levels. However, there is a lack of studies linked to the micro level, where the clothing factories are located. Thus, the study focused on a systematic literature review, relating the concepts and principles of CE to the apparel industry. As a result, a conceptual framework was developed from the junction of the 32 practices suggested in the 13 researched publications, divided into six stages, where each stage provides subsidies for the next. The framework contemplates all the productive stages, enabling the transition from the linear system to the circular one.